Konjac glucomannan-modified ferrous fumarate emulsions with interpenetrating polymer networks: Physicochemical stability, microstructure, and bioaccessibility - Tianyu Zhang; Fengru Zhang; Xintong Wang; Yuanting Wang; Mengting Jia; Zihan Ma; Yanbo Wang; Duoxia Xu (Food Hydrocolloids, 2027)

Betaine alleviates scleral remodeling in experimental myopia by regulating the TLR4/TAK1/NF-κB signaling pathway - Yinqiao Zhang; Yunxiao Xie; Zhaohui Yang; Runze Gao; Shuwen Yu; Jiawen Hao; Zhongyu Ma; Yuanting Yang; Ruixue Zhang; Hongsheng Bi; Dadong Guo (Toxicology and Applied Pharmacology, 2026)

Inverse-opal g-C3N4-supported halogen-regulated Bi2WO6/Bi2SiO5/BiOClxBr1-x heterostructures for simulated-sunlight-driven antibiotic degradation - Jingyue Hu; Yuanting Wu; Mato Knez; Lihui Guo; Cuicui Wang; Hulin Liu; Xinmeng Zhang; Ou Hai; Yunlong Xue (Journal of Environmental Chemical Engineering, 2026)

Permeability evolution of coal fracture during injection-induced shear slip - Zhe Zhou; Fan Wang; Zhaolong Ge; Yuanting Zhang (Geomechanics for Energy and the Environment, 2026)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

The dietary flavonoid quercetin protects against visual cortical synaptic remodeling and ferroptosis in experimental myopia via the KEAP1-NRF2 pathway - Miao Zhang; Ruixue Zhang; Yuanting Yang; Xiaoyue Zhao; Baoyuan Sun; Zhongyu Ma; Mengke Wu; Jizhao Xin; Xuewei Yin; Hongsheng Bi; Dadong Guo (Food Bioscience, 2026)

Endoplasmic reticulum stress–based ATF6 signaling pathway: evaluation of 4-PBA improving retinal state in myopic guinea pigs - Mengke Wu; Miao Zhang; Mingbin Tian; Weibo Pan; Xuexin Wang; Ruixue Zhang; Yuanting Yang; Zhongyu Ma; Zhaohui Yang; Yinqiao Zhang; Hongsheng Bi; Dadong Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Supranutritional dietary vitamin D3 promoted the skin wound healing in turbot, Scophthalmus maximus L. - Zhichu Chen; Yuanyuan Fang; Yuanting Li; Xinhua Chen; Mingzhu Pan; María Ángeles Esteban; Kangsen Mai; Yanjiao Zhang; Dong Huang (Aquaculture, 2026)

Effect of oxygen vacancies induced by doping rare earth metal elements (La³⁺, Ce³⁺/⁴⁺, Nd³⁺) in NaTaO3 thin films on photocatalytic and antibacterial properties - Cuicui Wang; Shuxian Dong; Ruixue Yin; Anqi Cai; Haoyu Li; Zhizun Yue; Hongxia Ren; Chuanli Zhang; Hairong Yin; Yuanting Wu (Journal of Environmental Chemical Engineering, 2026)

Study on the effect of air contamination in helium on the reliability of a Helium Joule-Thomson cryocooler - Pengcheng Qu; Zhichao Chen; Ziqi Wei; Yuanting Zhang; Jinjian Chu; Baoyu Yang; Xi Chen; Shaoshuai Liu (International Journal of Refrigeration, 2026)

High Carbohydrate Feeding Exacerbates Oxidative Stress and Intestinal Dysfunction in Red Seabream (Pagrus major) after Skin Wounding - Zhichu Chen; Yuanting Li; Yuanyuan Fang; Dong Huang; M. Ángeles Esteban; Yanjiao Zhang (Marine Biotechnology, 2026)

Polyphenol-mediated hierarchical porous hydrogel evaporators for accelerated water transport and reduced evaporation enthalpy - Xueqian Zhang; Hongtao Li; Bo Liang; Zikun Zou; Zhen Yang; Shaohui Xiong; Lei Yang; Xu Wang; Yang Chen; Yuanting Xu; Yiwen Li (Science Bulletin, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Pd-integrated nanostructured electrode-boosted direct ammonia borane fuel cells with power density of over 700 mW cm−2 - Wenxing Jiang; Yuanting Peng; Qiqi Wan; Endao Zhang; Junbo Hou; Xiaodong Zhuang; Changchun Ke (Chemical Engineering Journal, 2026)

A 29-year-old male with eosinophilic myocarditis and multisystem involvement: A diagnostic dilemma between EGPA and idiopathic hypereosinophilic syndrome - Shan Ma; Yanqing Hu; Shuaiye Liu; Jihua Wang; Kun Zhang; Yuanting Zhu; Yang Wu (Next Research, 2025)

Mechanistic insights into ozone-induced asthma exacerbation: role of oxidative stress and IL-33 - Xinyi Fang; Bin Pan; Yuanting Xie; Wenpu Shao; Jingyu Li; Dongyang Han; Xiaoqing Hong; Wenyue Tu; Yifan Zhao; Jiaojiao Wu; Yaning Zhu; Yubin Zhang; et al. (Journal of Hazardous Materials, 2025)

Adsorption of radioiodine by metal sulfides and relevant derivatives - Wei Zheng; Xiaoxuan Chen; Hao Xu; Duxia Li; Yuanting Zhang; Wanliang Yang; Meisong Xu; Dehong Gong; Mengkui Tian (Journal of Cleaner Production, 2025)

Construction of inhomogeneous bismuth-based heterojunctions with efficient interfacial charge transport: Bridging of BiOX - Yuanting Wu; Lihui Guo; Xuhua Liu; Xiaoying Wang; Jingyue Hu; Yunlong Xue; Ou Hai; Hulin Liu; Xinmeng Zhang; Weizhi Tian; Yongqiang Feng (Environmental Research, 2025)

Expediting the integration of China into the global rare disease drug development and approval - Jiatong Ding; Huiyao Huang; Yuning Wang; Yiru Hou; Guo Zhao; Yuanting Cai; Shuhang Wang; Xuebo Zhang; Ning Li (Science Bulletin, 2025)

Hollow Fe2O3-NiFe2O4 hetero-nanoframes coupled with N-doped graphene for boosted electrochemical water oxidation through optimizing intermediate bonding - Yuanting Li; Ya Zhang; Ruidong Shi; Xiaoxin Xu; Xue Wang; Gongbing Zhou (Chemical Engineering Journal, 2025)

Intelligent control of flap-type fin stabilizer for ship roll motion reduction - Wenhua Xu; Jialong Jiao; Guodong Xu; Miao Zhang; Yuanting Zou (Ocean Engineering, 2025)

Hydrology Modulates the Microplastics Composition and Transport Flux Across the River–Sea Interface in Zhanjiang Bay, China - Xiaoqing Chen; Peng Zhang; Jing Lu; Yuanting Chen; Jibiao Zhang (Journal of Marine Science and Engineering, 2025)
Estuaries act as significant pathways for plastic waste entry into the oceans, with microplastics (MPs) being intricately influenced by river and coastal hydrodynamics. MPs become entrapped within estuaries during transport, particularly at the river–sea interface, which impacted by tidal fluctuations. However, few studies have examined the role of the impacts of tidal variations on microplastic abundance and export flux at the river–sea interface across contrasting hydrological regimes (dry vs. wet seasons). In this study, we conducted observations to assess MPs abundance, composition, and flux in the Suixi Estuary of Zhanjiang Bay, China The results indicated an overall mean abundance of MPs of 91.1 ± 75.0 items/L, which was linked to tidal variations, decreasing during high tides and increasing during low tides. Transparent color, fibrous shape, and a size range of 100–330 μm were the most prevalent characteristics in water samples. MPs diversity was higher during the wet season compared to the dry season. In addition, the MPs influx was about 1.61 × 109 items/year from the river to the sea across both seasons. Additionally, hydrological regimes, tidal forces, and human activities were identified to influence MPs abundance and flux. This quantitative analysis establishes a mechanistic framework for understanding hydrological impacts on estuarine MPs transport, providing critical baseline data for developing targeted pollution management strategies in coastal ecosystems.

Robust mussel-inspired LBL carbon nanotube-based superhydrophobic polyurethane sponge for efficient oil–water separation utilizing photothermal effect - Guoyan Yang; Yuxin Zhang; Zuozhu Yin; Yuanting Deng; Zihao Li; Yu Xie; Yuhua Chen; Chenggang Yang; Haitao Yang; Yidan Luo; Zhen Hong; Mingshan Xue (Fuel, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

Construction of energy storage heterojunction and enhancement mechanism of dark and full-spectrum energy storage piezoelectric catalysis - Bixin Zhang; Guoqiang Tan; Wenlong Liu; Xiongtao Wu; Linxin Guo; Zeqiong Wang; Chunyan Zeng; Ying Liu; Tian Liu; Qian Yang; Ao Xia; Huijun Ren; et al. (Chemical Engineering Journal, 2025)

Exploring the response and prediction of phytoplankton to environmental factors in eutrophic marine areas using interpretable machine learning methods - Shimin Yang; Yuanting Ma; Jie Gao; Xiajie Wang; Futian Weng; Yan Zhang; Yan Xu (Science of The Total Environment, 2024)

Characteristics of Higher Harmonic Forces on Submerged Horizontal Cylinders with Sharp and Round Corners - Hongfei Mao; Jinwen Zeng; Guanglin Wu; Hanqing Chen; Shuqin Zhang; Yuanting Yang; Qinru Yang (Journal of Marine Science and Engineering, 2024)
In this study, a two-phase flow numerical wave tank model based on the viscous flow theory was applied to conduct computational research on the interaction between waves and submerged horizontal cylinders. The research objective is to reveal the hydrodynamic characteristics of nonlinear loads on submerged horizontal cylinders with a focus on vortex effects. The influence of the sharp and round corners of cross-sections on the wave forces on cylinders was summarized. The reasons for the characteristics of the wave forces were explained by analyzing the flow field distribution around the cylinder and decomposing the wave forces into inertial and drag forces. This study found that under the various incident wave amplitudes, the section corner and aspect ratio have significant impacts on each frequency component of the horizontal and vertical wave forces. The distribution of the vorticity field shows that the vortex effects lead to the differences between the loads on the cylinder under different cross-sectional corners and aspect ratios. The characteristics of inertial forces and drag forces on the cylinders were given by comparing and analyzing the cases with different sectional sharp and round corners. The inertia and drag coefficients were obtained by solving Morison’s equation. Under various Kc and Re numbers, the maximum values of the inertia and drag coefficients obtained are significantly different from those for submerged cylinders under oscillatory flow action.

Enhanced dewatering of dredging slurry by Fenton preoxidation and composite coagulants: optimization experiments and dewatering mechanisms - Xuyang Zhou; Jingwei Feng; Liu Zhang; Yulin Yang; Yuanting Xiao; Chunli Fan; Deqian Xu; Aiyong Zhang (Environmental Science and Pollution Research, 2024)

Sequence and epigenetic variations of R2R3-MYB transcription factors determine the diversity of taproot skin and flesh colors in different cultivated types of radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Xiangyu Wu; Wenyu Shi; Ningjie Chen; Yuanting Pang; Li Zhang (Theoretical and Applied Genetics, 2024)

Roles of extracellular vesicles on macrophages in inflammatory bone diseases - Yifan Lin; Ziyan Wang; Shirong Liu; Jiaohong Liu; Zhiyi Zhang; Yuanting Ouyang; Zhikang Su; Ding Chen; Lvhua Guo; Tao Luo (Molecular and Cellular Biochemistry, 2024)

A NAC Transcription Factor RsSND1 Regulating Secondary Cell Wall Deposition Involves in Fleshy Taproot Formation in Radish (Raphanus sativus L.) - Yanping Wang; Qingbiao Wang; Xiangyu Wu; Yuanting Pang; Yu Guo; Zixiong Li; Li Zhang (Journal of Plant Growth Regulation, 2024)

Prescribed-time observer-based sideslip compensation in USV line-of-sight guidance - Chunlai Yu; Junkang Zhu; Yuanting Hu; Hao Zhu; Ning Wang; Haohao Guo; Qinjin Zhang; Siyuan Liu (Ocean Engineering, 2024)

Thin and soft Ti3C2Tx MXene sponge structure for highly sensitive pressure sensor assisted by deep learning - Wang Guo; Zhiqiang Ma; Zhou Chen; Haojun Hua; Dong Wang; Mohamed Elhousseini Hilal; Yatian Fu; Pengyi Lu; Jian Lu; Yuanting Zhang; Derek Ho; Bee Luan Khoo (Chemical Engineering Journal, 2024)

Plasma-Free Blood as a Potential Alternative to Whole Blood for Transcriptomic Analysis - Qingwang Chen; Xiaorou Guo; Haiyan Wang; Shanyue Sun; He Jiang; Peipei Zhang; Erfei Shang; Ruolan Zhang; Zehui Cao; Quanne Niu; Chao Zhang; Yaqing Liu; et al. (Phenomics, 2024)
RNA sequencing (RNAseq) technology has become increasingly important in precision medicine and clinical diagnostics, and emerged as a powerful tool for identifying protein-coding genes, performing differential gene analysis, and inferring immune cell composition. Human peripheral blood samples are widely used for RNAseq, providing valuable insights into individual biomolecular information. Blood samples can be classified as whole blood (WB), plasma, serum, and remaining sediment samples, including plasma-free blood (PFB) and serum-free blood (SFB) samples that are generally considered less useful byproducts during the processes of plasma and serum separation, respectively. However, the feasibility of using PFB and SFB samples for transcriptome analysis remains unclear. In this study, we aimed to assess the suitability of employing PFB or SFB samples as an alternative RNA source in transcriptomic analysis. We performed a comparative analysis of WB, PFB, and SFB samples for different applications. Our results revealed that PFB samples exhibit greater similarity to WB samples than SFB samples in terms of protein-coding gene expression patterns, detection of differentially expressed genes, and immunological characterizations, suggesting that PFB can serve as a viable alternative to WB for transcriptomic analysis. Our study contributes to the optimization of blood sample utilization and the advancement of precision medicine research.

An ultra-high-temperature cavity receiver with a simple flat absorber for safe and efficient solar-thermal conversion - Jikang Wang; Yuanting Zhang; Yu Qiu; Qing Li (Journal of Cleaner Production, 2024)

Effects of shore-normal coastal structure on medium- to long-term embayed shoreline evolution - Jitao Yu; Yuanting Ding; Pei Liu; Renfu Fan; Lin Zhang (Acta Oceanologica Sinica, 2024)

Preparation of high-performance asymmetric supercapacitors based on NiCo2S4 nanospheres and CuO-MOF nanosheets on carbon fibers - Baopeng Liu; Jun Zhang; Jiawei Xu; Yanjie Pan; Yanshan Huang; Sheng Han; Yuanting Li (Fuel, 2024)

Optical-thermal-stress analysis of a multiscale solar receiver for ultra-high-temperature concentrating solar power - Yuanting Zhang; Qing Li; Yu Qiu (Journal of Cleaner Production, 2023)

Impacts of physical activity and particulate air pollution on the onset, progression and mortality for the comorbidity of type 2 diabetes and mood disorders - Huihuan Luo; Yuxin Huang; Qingli Zhang; Kexin Yu; Yuanting Xie; Xia Meng; Haidong Kan; Renjie Chen (Science of The Total Environment, 2023)

Cholinergic anti-inflammatory pathway mediates diesel exhaust PM2.5-induced pulmonary and systemic inflammation - Yuanting Xie; Shimin Tao; Bin Pan; Wenhui Yang; Wenpu Shao; Xinyi Fang; Dongyang Han; Jingyu Li; Yubin Zhang; Renjie Chen; Weihua Li; Yanyi Xu; et al. (Journal of Hazardous Materials, 2023)

Testosterone attenuates senile cavernous fibrosis by regulating TGFβR1 and galectin-1 signaling pathways through miR-22-3p - Zongren Hu; Yuanting Zhang; Jisong Chen; Min Luo; Neng Wang; Yinfu Xiao; Qinghu He (Molecular and Cellular Biochemistry, 2023)

Erosion hotspot identified along the sandy coast of Shanwei: characteristics and origin - Jitao Yu; Yuanting Ding; Lin Zhang; Pei Liu; Renfu Fan (Acta Oceanologica Sinica, 2023)

Highly active and durable nitrogen-doped CoP/CeO2 nanowire heterostructures for overall water splitting - Lili Zhang; Yuanting Lei; Wenjing Xu; Dan Wang; Yafei Zhao; Wenxing Chen; Xu Xiang; Xinchang Pang; Bing Zhang; Huishan Shang (Chemical Engineering Journal, 2023)

The role of PIWI-interacting RNA in naringin pro-angiogenesis by targeting HUVECs - Yixing Pi; Zitian Liang; Qianzhou Jiang; Ding Chen; Zhikang Su; Yuanting Ouyang; Zhiyi Zhang; Jiaohong Liu; Siyi Wen; Li Yang; Tao Luo; Lvhua Guo (Chemico-Biological Interactions, 2023)

A robust and 3D-printed solar evaporator based on naturally occurring molecules - Xueqian Zhang; Yu Yan; Ning Li; Peng Yang; Yiyan Yang; Gaigai Duan; Xu Wang; Yuanting Xu; Yiwen Li (Science Bulletin, 2023)

Techno-economic analysis of integrated carbon capture and utilisation compared with carbon capture and utilisation with syngas production - Yuanting Qiao; Weishan Liu; Ruonan Guo; Shuzhuang Sun; Shuming Zhang; Josh J. Bailey; Mengxiang Fang; Chunfei Wu (Fuel, 2023)

The role of Th17 cells: explanation of relationship between periodontitis and COPD? - Jiaohong Liu; Yuanting Ouyang; Zhiyi Zhang; Siyi Wen; Yixing Pi; Ding Chen; Zhikang Su; Zitian Liang; Lvhua Guo; Yan Wang (Inflammation Research, 2022)

Activation of the bitter taste sensor TRPM5 prevents high salt-induced cardiovascular dysfunction - Hao Wu; Yuanting Cui; Chengkang He; Peng Gao; Qiang Li; Hexuan Zhang; Yanli Jiang; Yingru Hu; Xiao Wei; Zongshi Lu; Tianyi Ma; Daoyan Liu; et al. (Science China Life Sciences, 2020)